Oxycodone Immediate Release for Cancer Pain Management in Turkey: Maximizing Value in Opioid Analgesics (Journal of Cancer Research Updates, 2014)
Cancer pain can be severe, yet is often undertreated. In many parts of the world, there is a reluctance to prescribe narcotics for analgesia. Since the World Health Organization first published its pain ladder  treatment paradigm in 1988, cancer pain is usually treated initially with nonopioids, then weak opioids, and finally strong opioids along with adjuvant agents as the pain intensifies. When initiating opioid therapy for cancer patients, the clinician must consider whether the patient is opioid naƒ¯ve or opioid experienced. For naƒ¯ve patients, opioid therapy must be started slowly, at a low dose initially, with adverse events anticipated and treated proactively. In all cases, opioid titration involves a controlled, stepwise increase of opioid dose until adequate (but not necessarily 100%) analgesia is achieved. A variety of opioid products are available, including immediate-release and controlled-release formulations. Immediate-releaseformulations are designed for easy titration to adequate analgesia; their rapid onset of action also makes them appropriate for managing breakthrough pain. Although morphine has long been considered the gold standard of cancer analgesics, oral oxycodone is increasingly used and is similar to morphine in efficacy and safety for cancer patients. Indeed, about 75% of morphine-tolerant patients can be successfully rotated to oxycodone. Adverse events with oxycodone are similar or perhaps favorable compared to those of other strong opioids. Because cancer pain can be challenging to treat, the addition of oral oxycodone IR is an important new tool for clinicians to consider when trying to control cancer pain.